(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article talks about the rules of creating a composition from different colored objects in painting, which is the main specialty of higher educational institutions specializing in fine arts, and the specific aspects of its work on a contrast background are analyzed.